(untitled) (Asian Journal of Social Science Studies, 2022)
Pragmatics studies the use of language in human communication in different social backgrounds and contexts (Mey, 2001). In the field of pragmatics, the analysis of speech act constitutes one of the majority of the related research (Austin, 1962). Speech act is significant to research the linguistic phenomena that occur in spoken language, particularly in movies. For this study, it choose the movie Love Actually as the data to investigate one of the speech acts, greeting. Love Actually is British famous romantic comedy, displaying love stories of various characters such as Prime Minister, singer, and writer. Focusing on greeting, the essay will discuss its classification based on Ebsworth et al. (2009), and combine with Brown and Levinson‟s (1987) politeness strategies to bring more implications to language education.